PERAN PONDOK PESANTREN DALAM MEMBANGUN MODERASI BERAGAMA MELALUI AKULTURASI BUDAYA ISLAM DAN TIONGHOA DI LASEM - Luthvia, Saudah; Nugroho, Puspo (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
This study examines the role of Islamic boarding schools in fostering religious moderation values through the cultural acculturation of Islam and Chinese traditions in Lasem's multicultural society. A qualitative descriptive approach was employed, with data collected from literature reviews, including books, articles, and scientific journals. The findings reveal that religious moderation serves as a foundational principle for achieving social harmony in Lasem, as reflected in the cultural acculturation visible in architecture, batik, traditions, and lifestyle. Key Islamic values, such as tawasuth (moderation), infitah (inclusivity), tawazun (balance), and musawah (equality), underscore this process, aligning with the concept of Islam as Rahmatan lil Alamin. Islamic boarding schools, particularly Pondok Pesantren Kauman, play a crucial role in integrating local cultural practices with Islamic teachings, offering a unique and harmonious model of diversity in a multicultural society. The study also emphasizes the importance of these institutions in promoting tolerance, understanding, and coexistence among different cultural and religious communities. These findings contribute significant insights for developing policies and strategies to advance religious moderation in Indonesia, particularly within diverse and multicultural environments. By highlighting Lasem as a case study, this research underscores the potential of cultural acculturation as a bridge for fostering unity in diversity.